HUMAN DIMENSIONS OF RELIGION IN ISLAM AND CHRISTIANITY - Anyanwu, Herbert Onyema (Journal of Dharma, 1989)
When one speaks of interaction one really means the action between one another while tolerance means to recognize and respect others’ beliefs, practices without necessarily agreeing or sympathizing. As is well known Nigeria is pluralistic as regards religion and as such the citizens are in much need of interaction and tolerance among one another. As a religious pluralistic country Nigeria has the following three dominating religions